The Effect of an Instructional Program based on Authentic Assessment on the Achievement of EFL Secondary Stage Jordanian Students Reading - Mohaidat , Mohammed (Jordan Journal of Educational Sciences, 2013)
The present study aimed at investigating the effect of an instructional program based on authentic assessment on the achievement of EFL secondary stage students in Jordan in the reading Skills through answering the following question: Is there a significant difference in Jordanian Secondary school students’ achievement in reading comprehension between the experimental group and the control group due to the method of assessment (Traditional or Authentic)? The study hypothesis was stated as follows: There is no statistically significant difference (α = 05) in Jordanian secondary school students’ achievement in reading comprehension between the experimental group and the control group due to the method of assessment. The subjects of the study consisted of 70 eleventh grade students who were divided into an experimental group and a control group. To examine the study hypothesis, the researcher developed an instructional program based on authentic assessment techniques to assess the experimental group students. The researcher also developed another program based on traditional assessment to assess the control group students. In addition, the researcher developed an achievement test to assess the subjects’ reading skills before and after conducting the experiment. Validity and reliability of the instruments were ensured. The experiment lasted for one semester (approximately three months). MANOVA and the t-test were used. The findings of the study showed that there was a statistically significant difference between the two groups on the reading achievement post-test in favor of the experimental group which was taught using authentic assessment techniques. In light of the findings of the study, the researcher proposed some recommendations to the Ministry of Education, EFL teachers, and researchers who are interested in authentic assessment